Impact of in-utero electronic cigarette exposure on neonatal neuroinflammation, oxidative stress and mitochondrial function - Archie, Sabrina Rahman; Sifat, Ali Ehsan; Mara, David; Ahn, Yeseul; Akter, Khondker Ayesha; Zhang, Yong; Cucullo, Luca; Abbruscato, Thomas J. (Frontiers in Pharmacology, 2023)
Despite the prevalence of the perception that electronic cigarettes (e-cig) are a safer alternative to tobacco smoke, growing concern about their potential toxic impact warrants adequate investigation focusing on special populations like maternal and pediatric groups. This study evaluated the consequences of maternal e-cig use on neonatal neuro-inflammation, oxidative stress, and mitochondrial function in primary cultured neurons and postnatal day (PD) 7 and 90 brain.Pregnant CD1 mice were exposed to e-cig vapor (2.4% nicotine) from gestational day 5 (E5) till PD7, and the primary neurons were isolated from pups at E16/17. Cellular total reactive oxygen species (ROS) and mitochondrial superoxide were measured in primary neurons using CM-H2DCFDA and Mitosox red, respectively. Mitochondrial function was assessed by Seahorse XF Cell Mitostress analysis. The level of pro-inflammatory cytokines was measured in primary neurons and PD7 and PD90 brains by RT-PCR and immunobead assay. Western blot analysis evaluated the expression of antioxidative markers (SOD-2, HO-1, NRF2, NQO1) and that of the proinflammatory modulator NF-κB. Significantly higher level of total cellular ROS (P <0.05) and mitochondrial superoxide (P <0.01) was observed in prenatally e-cig-exposed primary neurons.We also observed significantly reduced antioxidative marker expression and increased proinflammatory modulator and cytokines expression in primary neurons and PD7 (P <0.05) but not in PD90 postnatal brain. Our findings suggest that prenatal e-cig exposure induces postnatal neuroinflammation by promoting oxidative stress (OS), increasing cytokines' levels, and disrupting mitochondrial function. These damaging events can alter the fetal brain's immune functions, making such offspring more vulnerable to brain insults.